A Need Analysis of English Local Culture for Lopus Village Tour Guide - Marchelya, Aninda; Dangin, Dangin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study examines the necessity of English proficiency tailored to local culture for tour guides in Lopus Village, a rising tourism destination. With the increasing interest of international visitors, mastering English that integrates cultural elements becomes vital for effective communication and promoting local heritage. Using a qualitative research design, data were gathered through interviews, observations, and questionnaires involving local tour guides. The findings reveal specific language needs that align with the village’s cultural uniqueness, highlighting the importance of English for Specific Purposes (ESP) and integrated English skills for the tourism sector. This study underscores the significance of a needs-based approach to language training in local tourism.